Lack of Spinal Neuropeptide Y Is Involved in Mechanical Itch in Aged Mice - Cui, Huan; Su, Wenliang; Cao, Yan; Ma, Lulu; Xu, Guangyan; Mou, Wanying; Zhang, Hanlin; Yu, Jiawen; Ma, Chao; Zhang, Xiuhua; Huang, Yuguang (Frontiers in Aging Neuroscience, 2021)
Neuropeptide Y (NPY) signaling plays an essential role in gating the pruritic afferent information in the spinal cord. Recent studies revealed that the aging process downregulated the expression of NPY in the central nervous system. We propose that the lack of spinal NPY may be involved in certain types of pruritus in the elderly population. This study was designed to investigate the role of NPY in aging-induced itch using the senile mouse model. The expression of NPY in the spinal dorsal horn was compared between the young (2 months old) and aged (24 months old) mice. Western blotting and immunohistochemistry showed that the expression of NPY was significantly reduced in the spinal dorsal horn in the aged mice. In addition, a neuronal maker of apoptosis, TUNEL was detected in the NPY-immunopositive neurons only in the aged spinal cord. Behavioral assay indicated that light mechanical stimulus evoked significantly more scratching in the aged-as compared to the young-mice, while chemical-evoked itch and pain-related behaviors were not altered. Intrathecal injection of either NPY or LP-NPY, an NPY receptor 1 (NPY1R) agonist, significantly alleviated the mechanically-evoked itch in aged mice without altering the responses to chemical pruritogens. Our study suggested that an downregulation of spinal NPY in the aged mice might play a role in the higher incidence of mechanically-evoked itch as compared to the young mice. Therapies targeting the NPY system might serve as a potential strategy for alleviating the pruritic symptoms among the elderly population.